DESENVOLVIMENTO DE MATERIAIS DIDÁTICOS PARA O PRÉ-NATAL PEDIÁTRICO: WEBSITE, PRODUÇÃO AUDIOVISUAL E FOLDER PARA A PROMOÇÃO DA SAÚDE MATERNO-INFANTIL - Pinheiro, Luísa Mendonça de Souza (2024)
The pediatric prenatal visit is a strategic opportunity to guide families on the management of the newborn, strengthening bonds and promoting comprehensive health. Objective: To develop and validate educational strategies to strengthen the pediatric prenatal visit, including an interactive Web site, a series of informative videos and teaching material in folder format - classified as T1 in the technical-technological typology of CAPES. Methodological approach: Methodological study subdivided into four stages: 1) Scoping review to identify scientific evidence and guidelines on the subject; 2) Situational diagnosis, carried out with 35 puerperal women and 28 health professionals, mapping weaknesses in prenatal guidance and the specific needs of the target audience; 3) Preparation of the didactic materials folder, series of videos and WebSite; 4) Initial validation with specialists in maternal and child health. Results: The results show significant gaps in prenatal guidance, with less than 60% of puerperal women receiving essential information. The folder covers topics such as breastfeeding, umbilical stump management and newborn safety, while the website and videos complement it with interactive and accessible content. The qualitative analysis revealed that mothers face common doubts, such as general care and management of risk situations, while professionals highlighted the importance of a support network for pregnant women. The products developed have practical applicability: the folder offers organized and objective information on breastfeeding, umbilical stump management, safe transport, among other essential topics, while the website expands access to interactive and up to-date content, with short, subtitled videos, accessible to hearing-impaired individuals and designed for families' daily lives. These materials are intended not to replace, but to enhance verbal guidance, promoting greater autonomy and confidence for families. The extended validation stage is planned to include evaluation by specialists and pregnant women, ensuring relevance, clarity and cultural applicability. Final considerations: The products developed can be considered innovative and have the potential to be replicated, qualifying pediatric prenatal care, promoting health education that is inclusive, accessible and in line with contemporary demands. In this way, the research dialogues directly with the ONU Sustainable Development Goals (SDGs), especially SDG 3 (Health and Well-being), SDG 4 (Quality Education) and SDG 10 (Reducing Inequalities), contributing to the dissemination of safe and accessible information for pregnant women, families and health professionals. These materials represent a contribution to public health, with a potential impact on reducing neonatal morbidity and mortality and increasing the confidence and autonomy of families during neonatal care.